Potassium dynamics in soil and soybean potassic nutrition - Rosolem, Ciro Antonio; Bessa, Antonio Marcos; Pereira, Hélio Fernandes Marques (Pesquisa Agropecuaria Brasileira, 1993)
Potassium deficiency in soybeans has spread in São Paulo State, Brazil, as a consequence of soil K reserve depletion. Exchangeable and nonexchangeable K dynamics in soil were investigated in order to understand the reserve exaustion and its significance to soybean nutrition. Soybean was grown in 81 pots with five soils differing in K and clay contents, in presence or absence of K fertilization. Soil samples, were taken at 20 days interval and soybean was harvest at R6. Exchangeable (H2SO4 0,05 N) and nonexchangeable K (boiling HNO3) were estimated in soil sample. Two of the soils were very poor in exchangeable K, and even so there was no response in dry matter due to K fertilization. In spite of some differences in K contents in some of the soybeans parts, generally K absorption was not affected by K fertilization, except in grains. Potassium acumulation in soybean plants were affected by soils, but the response was not closely related to exchangeable K in soil. The main K source to the plants was the HNO3 extrated K, showing that this form is not at all nonexchangeable. After the period of maximum plant demand there was a sharp increase in extractable K in soil showing a tendency to a natural equilibrium.
Keywords: nonexchangeable K; exchangeable K; K absorption